Answer:
The vertex of the function
is (h,k) = (3 , -1)
Solution:
The vertex form of quadratic equation is generally given as,
![f(x) = a(x - h)^(2) + k](https://img.qammunity.org/2020/formulas/mathematics/middle-school/branghygfi90q2d4ibzso43zpv1vokrv0t.png)
Where h,k is the vertex of the parabola.
From question, given that
.
we have to find the vertex of the function.
Let us first convert the given quadratic equation to vertex form (eqn 1)
![x^(2)-6 x=-8](https://img.qammunity.org/2020/formulas/mathematics/middle-school/k76ji18v31c86v9mmaa3h7dnmp6s65as8e.png)
By adding “9” on both sides of equation, we get
![x^(2)-6 x+9=-8+9](https://img.qammunity.org/2020/formulas/mathematics/middle-school/rq5r4tfmy2r8njynrapcedj1x98enynx94.png)
![x^(2)-6 x+9=1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/wiuc1ez2evoel2qx7xlf4wog934a6wil8j.png)
By using the identity
,the right hand side of above equation becomes,
![(x-3)^(2)=1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/wy8cf19ws9hx9mjvy2gu2swjbii5366uz8.png)
![(x-3)^(2)-1=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/gvrxopymv1hojcdpc2wyn8f648xuvxsjc2.png)
Now,the equation
is of the vertex form.
By comparing
with
![a(x-h)^(2)+k](https://img.qammunity.org/2020/formulas/mathematics/middle-school/8ctvsp5067t1cu2gulhyqut6wt6cwjyr47.png)
we get the values of (h,k)
a = 1; h = 3; k = -1
hence the vertex of the function
is (h,k) = (3 , -1)